Tackling health literacy: adaptation of public hypertension educational materials for an Indo-Asian population in Canada - Mohan Sailesh; Smith Megan; Allu Selina; King Kathryn M; Mawani Shefina; Jones Charlotte A; Campbell Norman RC (BMC, 2011)
Abstract Background Indo-Asians in Canada are at increased risk for cardiovascular diseases. There is a need for cultural and language specific educational materials relating to this risk. During this project we developed and field tested the acceptability of a hypertension public education pamphlet tailored to fit the needs of an at risk local Indo-Asian population, in Calgary, Alberta, Canada. Methods A community health board representing Calgary's Indo-Asian communities identified the culturally specific educational needs and language preferences of the local population. An adaptation of an existing English language Canadian Public Hypertension Recommendations pamphlet was created considering the literacy and translation challenges. The adapted pamphlet was translated into four Indo-Asian languages. The adapted pamphlets were disseminated as part of the initial educational component of a community-based culturally and language-sensitive cardiovascular risk factor screening and management program. Field testing of the materials was undertaken when participants returned for program follow-up seven to 12 months later. Results Fifty-nine English-speaking participants evaluated and confirmed the concept validity of the English adapted version. 28 non-English speaking participants evaluated the Gujarati (N = 13) and Punjabi (N = 15) translated versions of the adapted pamphlets. All participants found the pamphlets acceptable and felt they had improved their understanding of hypertension. Conclusions Involving the target community to identify health issues as well as help to create culturally, language and literacy sensitive health education materials ensures resources are highly acceptable to that community. Minor changes to the materials will be needed prior to formal testing of hypertension knowledge and health decision-making on a larger scale within this at risk community.